Inhibitory effect of n-hexane: ethyl acetate fraction from Artemisia vulgaris L. on cell culture of oral epithelial carcinoma - Ira Arundina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Sudamala herb (Artemisia vulgaris L.) is often used in society as an anti tumor for organs of digestive system including oral cavity. Nevertheless, there are still no further scientific researches on active materials which can be used as anti carcinogen in oral cavity. Most of anti carcinogens are actually obtained from the genus Artemisia. Moreover, in Indonesia, the species of the genus Artemisia that grows the most is Artemisia vulgaris L. The problem of this research, however, is that the effect of n-hexane fraction: ethyl acetate from Artemisia vulgaris L. towards the decreasing of oncogene in oral squamous cell carcinoma is still indefinite. Purpose: The objective of this research is to explain the effect of giving n-hexane : ethyl acetate (3:7) fraction containing terpenoid from Artemisia vulgaris L. towards the decreasing of oncogene in oral epithelial carcinoma cell line. Methods: The method of this research is laboratory experimental research by using squamous cell carcinoma of oral cavity on cell culture. The inhibitory percentage test in vitro, furthermore, is taken during the analysis. The result then is analyzed by probit analysis with drawing relation curve between the inhibitory percentage and concentration. Result: The result of n-hexane : ethyl acetate (3:7) fraction containing terpenoid from Artemisia vulgaris L. has the smallest IC50, 3.902 μg/ml, less than 20 μg/ml suitable with NCI criteria; thus, it can potentially be used as anti carcinogen. Conclusion: There is the decreasing of oncogenes after being given n-hexane : ethyl acetate (3:7) fraction containing terpenoid from Artemisia vulgaris L. towards oral epithelial carcinoma cell line.